IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL (SPMI) DI SMA NEGERI 7 GOWA KABUPATEN GOWA - Hardianti Rukmana; Wahira; Ansar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the internal quality assurance system in the educational unit at SMA Negeri 7 Gowa, and to analyze the supporting and inhibiting factors in the implementation of the quality assurance system at SMA Negeri 7 Gowa. This research is classified as a qualitative study. The data sources used were primary and secondary data, with data collected through interviews, documentation, and observation. Data validity was established using triangulation techniques. Data analysis techniques involved data reduction, data presentation, and conclusion drawing. The results show that the SPMI (Internal Quality Assurance System) implementation process at SMA Negeri 7 Gowa is carried out through 5 stages that form a continuous, revolving cycle. This cycle runs for one academic year. The five stages are: standard setting, quality mapping, quality fulfillment planning, quality fulfillment implementation, and quality evaluation/audit. The improvement of the Internal Quality Assurance System Implementation at SMA Negeri 7 Gowa can be viewed as follows: 1) Input consists of standards for educators and educational staff, infrastructure and facility standards, financing standards, and management standards; 2) Process consists of the learning process, learning content, and learning assessment; 3) Output consists of graduate standards. Supporting factors were found to aid in the successful completion of all stages of SPMI activities at SMA Negeri 7 Gowa. The implication of this study is that the implementation of quality assurance at SMA Negeri 7 Gowa needs to be continuously optimized, as optimal SPMI will lead toward Continuous Quality Improvement (CQI).